2019
DOI: 10.29309/tpmj/2019.26.12.3314
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Diabetic patients about Insulin injection technique.

Abstract: Diabetes mellitus is leading cause of morbidity and mortality worldwide. Most of them are due to its macro and microvascular complication. Objectives: To determine the accuracy of insulin injection technique in adult diabetic patients between age of 20 to 50 years on insulin therapy for ≥02 years. Study Design: Cross sectional study. Settings: Pakistan Institute of Medical Sciences, Islamabad. Period: From March to August, 2016. Subjects: All diabetic patients between age 20 to 50 years and on insulin therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Study revealed that approximately 70% of the patients had insufficient awareness about injection technique. 8 Aligned with the global data, according to preliminary survey with the experts (for the survey’s method see section “Recommendations from the Advisory Board Meeting”), approximately one-third of their patients used needle more than six times and there was still <25% of their patients with adequate knowledge of injection technique. Improper injection technique and the choice of injection sites could alter insulin absorption, resulting in uncontrolled blood glucose levels (hyperglycemia/hypoglycemia), and lipohypertrophy (LH).…”
Section: Implementing Proper Injection Techniques and Improved Needle...mentioning
confidence: 99%
See 3 more Smart Citations
“…Study revealed that approximately 70% of the patients had insufficient awareness about injection technique. 8 Aligned with the global data, according to preliminary survey with the experts (for the survey’s method see section “Recommendations from the Advisory Board Meeting”), approximately one-third of their patients used needle more than six times and there was still <25% of their patients with adequate knowledge of injection technique. Improper injection technique and the choice of injection sites could alter insulin absorption, resulting in uncontrolled blood glucose levels (hyperglycemia/hypoglycemia), and lipohypertrophy (LH).…”
Section: Implementing Proper Injection Techniques and Improved Needle...mentioning
confidence: 99%
“…Education about DM has been widely recognized as an effective approach to managing and preventing the DM. 8 …”
Section: Implementing Proper Injection Techniques and Improved Needle...mentioning
confidence: 99%
See 2 more Smart Citations